The Content of Taxes and their Importance in Society - Kunduzova K. I (Research Parks Publishing LLC, 2021)
The concept of tax as an economic category is directly related to the emergence of the state and the duration of its activities. In this regard, it should be noted that the tax category arises as an economic reality through the state economic policy. The concept of tax in a narrow sense represents the proceeds of money levied by compulsory procedure from taxpayers at the disposal of the state.